Business Environment and Creative Industries in Romania - Clara Volintiru; Dumitru Miron (Amfiteatru Economic Journal, 2015)
This article explores the curent situation of creative industries in Romania, a field still insufficiently investigated where entrepreneurship is increasingly present. In this sense, it addresses addresses two research objectives. Taking as reference the relevant academic literature, and based on the analysis of an original data-set regarding the composition and structure of creative industries in Bucharest, the article propose a conceptual framework addapted to the context of Romania for the study of the structural mechanisms that ties the economic model and the development of those economic activities labeled as creative. Our findings suggest that the development tendencies of variou creative specialisations have a massive growth potential in the future, impacting deeply the Romanian business environment and entrepreneurial perspectives. The paper furthers the understanding of the role and characteristics of creative activities in the economy and creates the premises for comparative research projects in the future.
Keywords: M21; O10; O30; O35; 330; creative industries; entrepreneurship